In, not of: The theological task and the mission of the church - Tyler, Kate (Missiology, 2018)
This article demonstrates how an interdisciplinary approach to thinking about mission allows for a more dynamic definition of who belongs to the Christian community. It argues that the church ought to understand its relationship to its sociocultural environment not in terms of who is "in" and "out" but in terms of the One toward whom this community is oriented, and the corresponding movement towards or away from this center. This will be done by bringing the exegesis of John 17:14-19 and Romans 12:1-2 into an interdisciplinary dialogue with Paul Hiebert's "bounded-set" and "centered-set" models in order to show how the centered-set model provides a more theologically nuanced and faithful depiction of the church's missional identity. Additionally, the trinitarian theologies of Thomas Torrance and Lesslie Newbigin will be added to this conversation to further demonstrate how Hiebert's centered-set model, in partnership with a trinitarian ecclesiology which focuses upon participation, fellowship, and communion, reduces the stark divide of "in" and "out," instead defining belonging to the Christian community with reference to the God who gathers and calls the church together.